Digital Academic Certification with Blockchain: A Secure, Privacy-Preserving Prototype Using Hyperledger Fabric - Blanco, Pablo; Betarte, Gustavo; Luna, Carlos; Molina, María Fernanda (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC); 2025: Anais Estendidos do XIV Latin-American Symposium on Dependable and Secure Computing, 2025)
Academic certificates are essential credentials for students, universities, and third parties seeking to verify academic degrees. Traditional paper-based processes are susceptible to forgery, require manual checks, and cause delays and higher costs. This work introduces a prototype for digital academic certification using blockchain technology, specifically Hyperledger Fabric, emphasizing security, privacy, traceability and, regulatory compliance, particularly in relation to data protection laws like GDPR. The system uses private data collections, role-based access controls, and auditable transactions to maintain data minimization and accountability. Verification relies on hash matching, so sensitive data remains off-chain. The architecture clearly defines ecosystem roles—administrators, students, graduates, and verifiers—and considers interoperability with national and regional systems. Our qualitative assessment indicates that a permissioned blockchain can enhance trust and traceability, although challenges remain in scalability, governance, and adoption. We believe that a privacy-preserving blockchain-based certification system is feasible and could reinforce education infrastructure when integrated with existing digital and data protection policies.